Characterization and typology of goat production systems in the Southern Highlands of Peru - Sessarego Dávila, Emmanuel Alexander (2025)
Background and Aim: Characterizing local animal production systems is crucial for sustainable livestock development. This study aimed to characterize the diversity of goat production systems in the Highlands of Chincha province, Ica, Peru. Materials and Methods: A structured questionnaire was used to gather data from 82 goat breeders in three districts: San Juan de Yanac, San Pedro de Huacarpana, and Chavín. Factor analysis of mixed data and hierarchical classification analysis were conducted to identify typologies of goat production systems using R version 4.4.2. Results: Four distinct goat production types were identified, primarily differentiated by feeding location and deworming frequency. Type 2 (41.5%) was the most prevalent, characterized by grazing on breeders own land, minimal milk production (<1 liter/day, 91.2%), and a focus on cheese and goat kid sales (70.6%). Breeders were predominantly women, with limited resources and extensive management systems. Across all types, mixed breeding was common, and economic reliance on livestock and agriculture prevailed. Conclusion: Despite their diversity, all goat production systems shared extensive management practices and resource constraints, resulting in low productivity. These findings highlight the need for targeted public policies to improve productivity and sustainability in goat farming within the Ica region.